(untitled) (World Economics and Finance Bulletin, 2025)
The current research aims to identify the impact of strategic leadership in achieving organizational excellence among a sample of employees in the Diyala Municipalities Directorate, as strategic leadership was adopted as an independent variable expressed in dimensions ( formulating the strategic vision, Developing human capital, exploring core competencies, improving organizational culture, establishing ethical behaviors, The establishment of a control system ), and organizational excellence is a responsive variable expressed in dimensions (leadership excellence, service excellence, cognitive excellence), for the purpose of knowing and realizing the extent of interest that the organization under study has for the research variables and dimensions. The Diyala Municipalities Directorate was chosen as the field of the current research and its community represents all employees, numbering (137) individuals, while the research sample was (102) in the organization and the questionnaire was distributed to (110) individuals, as (8) invalid questionnaires were excluded, and (102) valid questionnaires were approved for analysis that represented the research sample. In accordance with the objectives that the current research aims to achieve and the type of hypotheses, the research adopted the descriptive analytical approach because it is one of the most important approaches suitable for studying behavioral and social phenomena, and based on the questionnaire as one of the main tools in collecting data, which included (45) paragraphs, and in an effort to analyze the data obtained, the researcher used a number of methods to diagnose the variables of the current research and describe them based on the statistical program ( Spss, Ver. 26 ) and ( Amos, Ver. 24 ) were used to verify the validity of the hypotheses formulated to answer the research questions. The research reached several diverse conclusions, the most important of which is that there are two significant correlation and influence relationships between strategic leadership in its combined dimensions and organizational excellence in its combined dimensions in the organization under study. This means that the more the dimensions of strategic leadership are adopted, the more the dimensions of organizational excellence are adopted